Feasibility of a real-time self-monitoring device for sitting less and moving more: a randomised controlled trial. Issue 1 (11th October 2017) - Martin, Anne; Adams, Jacob M; Bunn, Christopher; Gill, Jason M R; Gray, Cindy M; Hunt, Kate; Maxwell, Douglas J; van der Ploeg, Hidde P; Wyke, Sally; Mutrie, Nanette
Abstract : Objectives: Time spent inactive and sedentary are both associated with poor health. Self-monitoring of walking, using pedometers for real-time feedback, is effective at increasing physical activity. This study evaluated the feasibility of a new pocket-worn sedentary time and physical activity real-time self-monitoring device (SitFIT). Methods: Forty sedentary men were equally randomised into two intervention groups. For 4 weeks, one group received a SitFIT providing feedback on steps and time spent sedentary (lying/sitting); the other group received a SitFIT providing feedback on steps and time spent upright (standing/stepping). Change in sedentary time, standing time, stepping time and step count was assessed using activPAL monitors at baseline, 4-week follow-up (T1) and 12-week (T2) follow-up. Semistructured interviews were conducted after 4 and 12 weeks. Results: The SitFIT was reported as acceptable and usable and seen as a motivating tool to reduce sedentary time by both groups. On average, participants reduced their sedentary time by 7.8 minutes/day (95% CI −55.4 to 39.7) (T1) and by 8.2 minutes/day (95% CI −60.1 to 44.3) (T2). They increased standing time by 23.2 minutes/day (95% CI 4.0 to 42.5) (T1) and 16.2 minutes/day (95% CI −13.9 to 46.2) (T2). Stepping time was increased by 8.5 minutes/day (95% CI 0.9 to 16.0) (T1) and 9.0 minutes/day (95% CI 0.5 to 17.5) (T2). There were no between-group differences at either follow-up time points. Conclusion: The SitFIT was perceived as a useful tool for self-monitoring of sedentary time. It has potential as a real-time self-monitoring device to reduce sedentary and increase upright time.